Adolescent Health and Parents' and Teachers' Beliefs about Smoking: A Cross-Sectional Study - Francisco Carrión-Valero; Joan Antoni Ribera-Osca; José M. Martín-Moreno (MDPI AG, 2024)
Background: The acquisition of healthy lifestyle habits by adolescents is largely influenced by close interpersonal relationships including their parents and teachers. Methods: A cross-sectional survey regarding tobacco use was conducted among 304 parents and 41 teachers of secondary school adolescents (12-17 years of age) enrolled in the first, second, and third grades of compulsory secondary education at the largest high school in Sueca, Valencia, Spain. Results: The prevalence of smoking was 36.2% among parents (occasional smokers 75.4%) and 19.5% among teachers (occasional smokers 62.5%). Most parents (89.8%) did not believe that their child smoked and 95.7% viewed it negatively if they did. Also, 75.2% of parents agreed that tobacco consumption encourages adolescents to use cannabis or other drugs. Friends who smoke and additives added to cigarettes were considered very influential factors for starting smoking. Most teachers (90.2%) reported having given a recommendation to their students to quit smoking. Cannabis and cigarette smoking were rated as harmful to health. Most respondents believed that cigarette smoking may favor the consumption of cannabis. Conclusions: The use of e-cigarettes was also considered a risk factor for starting smoking. It would be advantageous incorporating parents and teachers as role models in multidisciplinary interventions addressing smoking behavior in secondary school students.